Effects of Gamification in an Academic History Course, 2010-2020 - Exam results from an academic first-cycle course in History, 2010-2020 - Svanberg, Mikael (Karlstad University, 2023)
The material consists of exam results among 458 students who for the first time answered a certain written exam on the last of four modules in an academic first-cycle (undergraduate) course in history at a Swedish university, distributed across ten course instances over eleven years, 2010-2020. The exam results consist of a score divided into points received on answers to the written exam and on points that each student was able to obtain from optional hand-in assignments before the written exam (quizzes). The material also contains information about the exam results from the two immediately preceding modules on the same course and at the same course instance. The data have been used to examine the extent to which the quizzes have affected the result on the final written exam and the extent to which the outcome has been affected by the examination result on the two immediately preceding modules.

Exam results from 458 students at a Swedish university, collected from ten course instances over eleven years, 2010-2020. Data have been collected from correction protocols 2010-2017 and from LADOK (Local Edp based documentation system) 2018-2020, after which the data have been anonymized. The variables are: study group, student category, examinee, sex and five outcome variables

Materialet består av tentamensresultat bland 458 studenter som för första gången besvarade en viss salsskrivning på den sista av fyra delkurser i en akademisk grundkurs i historia vid ett svenskt universitet, vid något av tio kurstillfällen mellan 2010 och 2020. Tentamensresultatet utgörs av en poängsumma fördelad på poäng som erhållits på svar salsskrivningens frågor respektive på poäng som varje student innan salsskrivningen har kunnat erhålla från frivilliga inlämningsuppgifter, kallade duggor. Materialet innehåller även uppgift om tentamensresultatet från de två närmast föregående delkurserna på samma kurs och vid samma kurstillfälle. Data har använts för att undersöka i vilken grad duggorna har påverkat resultatet på den sista salsskrivningen samt i vilken grad utfallet har påverkats av tentamensresultatet på de två närmast föregående delkurserna.

Examensresultat av 458 studenter vid ett svenskt universitet, insamlade vid tio kurstillfällen under elva år, 2010-2020. Data har inhämtats från rättningsprotokoll för åren 2010-2017 respektive från LADOK 2018-2020 samt har därefter anonymiserats. Variablerna är: studiegrupp, studentkategori, tentand, kön, tentamensår samt fem resultatvariabler
Effects of Gamification in an Academic History Course, 2010-2020 - Exam results from an academic first-cycle course in History, 2010-2020
Keywords: Behavior and Behavior Mechanisms; Beteende och beteendemekanismer; Education; Utbildning; ACHIEVEMENT; PRESTATIONER; MOTIVATION; MOTIVATION; action with an object; aktivitet med objekt; Higher and further education; Gymnasial och högre utbildning; HISTORY; HISTORIA; Didactics; Didaktik; History; Historia